Voting with Their Money: Brexit and Outward Investment by UK Firms - Holger Breinlich; Elsa Leromain; Dennis Novy; Thomas Sampson (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the impact of the 2016 Brexit referendum on UK foreign direct investment. Using the synthetic control method to construct appropriate counterfactuals, we show that by March 2019 the Leave vote had led to a 17% increase in the number of UK outward investment transactions in the remaining EU27 member states, whereas transactions in non-EU OECD countries were unaffected. These results support the hypothesis that UK companies have been setting up European subsidiaries to retain access to the EU market after Brexit. At the same time, we find that the number of EU27 investment projects in the UK has declined by around 9%, illustrating that being a smaller economy than the EU leaves the UK more exposed to the costs of economic disintegration.
Keywords: F15; F21; F23; 330; Brexit; foreign direct investment; synthetic control method